2020
DOI: 10.1186/s12903-020-01167-7
|View full text |Cite
|
Sign up to set email alerts
|

“Clinical comparison of bond failure rate between two types of mandibular canine-canine bonded orthodontic retainers- a randomized clinical trial”

Abstract: Background: Bonded retainers are widely used as they are esthetically pleasing, easily acceptable, provide greater stability, compliance free and causes no soft tissue irritation and speech problems. Though, fracture and bond failure are their shortcomings. Therefore, the objectives of this study were to evaluate the number of bond failures and type of failure pattern between two types of mandibular canine-canine bonded retainers. Methods: Total 60 subjects were recruited initially and were assessed for eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…No significant differences in plaque nor calculus accumulation were found between the wires.The smallest differences in the mandibular irregularity index were observed in patients with thin spiral wire bonded to all teeth, and the largest in patients with thick plain wire bonded only to canines and in patients with removable retainers. Nagani et al 2020 [ 28 ] RCT Comparison of failure rate and evaluation of failure pattern in 2 types of mandibular canine-canine bonded retainers. 52 patients (8 W, 44 M), 26 patients per group The adhesion to single dental element was considered separately Fiber reinforced composite retainers (INOD, U.P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences in plaque nor calculus accumulation were found between the wires.The smallest differences in the mandibular irregularity index were observed in patients with thin spiral wire bonded to all teeth, and the largest in patients with thick plain wire bonded only to canines and in patients with removable retainers. Nagani et al 2020 [ 28 ] RCT Comparison of failure rate and evaluation of failure pattern in 2 types of mandibular canine-canine bonded retainers. 52 patients (8 W, 44 M), 26 patients per group The adhesion to single dental element was considered separately Fiber reinforced composite retainers (INOD, U.P.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning bonding failures statistically significant differences concerning failure rates, discoloration and calculus accumulation [ 29 ] have been reported between retainers bonded with additional use of a bonding agent versus retainers bonded with a composite material only [ 29 , 36 ]. Adhesive failure (with no retained composite material on enamel surface) is the most common type of bond failure observed in fixed lingual retainers [ 28 , 42 ] Concerning the stability of dental alignment, irregularity index increases with time despite the presence of bonded retainers [ 25 , 27 , 41 ]. No difference has been confirmed as far as type of wire and splint was concerned.…”
Section: Resultsmentioning
confidence: 99%
“…Bearn [ 23 ] suggested that the retainer wires should preferably have low thickness and multiple braided strands. Nagani [ 24 ] reported lower failure rate of multistrand retainers compared with reinforced retainers. Also, multistrand retainers have less adverse effects on the periodontal tissue (such as inflammation or gingival recession) and lower risk of caries [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…L'avantage de cette technique est son faible coût et sa réalisation aisée en cabinet si la structure et l'équipement le permettent. Plusieurs auteurs 14,17,18,21 ont analysé et comparé les attelles en résine renforcées par des fibres, qui sont des alternatives fiables aux fils métalliques collés lorsqu'elles sont parfaitement réalisées et collées, mais il n'existe pour le moment aucune étude concernant les attelles imprimées en 3D ou usinées, leur tenue dans le temps n'est pas encore évaluée et il y a peu de recul sur cette technique toutefois prometteuse. Il faudra également évaluer la mobilité physiologique permise par ce système, qui est bien plus rigide qu'un fil métallique collé, sans toutefois avoir la rigidité d'une attelle métallique.…”
Section: Attelles En Résine En Impression 3dunclassified